Evaluating the antiproteinuric efficacy of cilnidipine in diabetic kidney disease - Sharma, Taruna; Tausif, Aalia; Ahmad, Sohaib (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetic kidney disease is a life threatening and disabling complication of uncontrolled diabetes mellitus. Clinical proteinuria is a well-established marker of renal dysfunction. A dual L/N-type calcium channel blocker cilnidipine dilates the afferent and efferent arterioles of the glomerulus decreasing the intraglomerular pressure and showing antiproteinuric effects. The present study was conducted to assess the antiproteinuric efficacy of cilnidipine in patients of diabetic kidney disease. Methods: This interventional study was conducted on 50 patients of both genders aged 18 years and above with diabetic nephropathy (stage-2 to stage 4) visiting the medicine OPD at HIMS, Dehradun over a period of six months, the patients were given tablet cilnidipine (5-20 mg) once or twice a day. Baseline urine protein creatinine ratio (UPCR), serum creatinine and the estimated glomerular filtration rate (eGFR) was recorded at baseline and repeated after a period of 12 weeks. The end point was the decrease in UPCR after a period of 12 weeks. Students-paired T test was used for analysing the intragroup data. Results: After 12 weeks of treatment with cilnidipine, a significant reduction was observed in the urinary protein creatine ratio (mean±SD) from 3.2±1.23 at baseline to 3.09±1.09 respectively (p<0.05). Along with this there was also a reduction in the in serum creatinine which was significant (p<0.05) as well as an increase in the eGFR value which was also statistically significant (p<0.001). Conclusions: Cilnidipine reduces the UPCR as well as improves the kidney function in patients with diabetic kidney disease.